Circulatory Shock - Dr. Ehsan ul Haq (Journal of University Medical & Dental College, 2020)
“Shock occurs when there is circulatory failure that results in inadequate cellular oxygen, that is arterial blood flow is inadequate to meet tissue metabolic needs.” Tissue oxygenation is dependent upon, cardiac output, hemoglobin saturation and peripheral micro circulation.